Modeling and analysis of the acidizing process in carbonate rocks using a two-phase thermal-hydrologic-chemical coupled model. (2nd November 2019) - Liu, Piyang; Yan, Xia; Yao, Jun; Sun, Shuyu
Highlights: A two-phase T-H-C coupled model is developed to simulate the dissolution process during carbonate acidization. A new model that describes the change of relative permeability curve as dissolution proceeding is proposed. A method for generating the initial porosity field with controllable correlation length is presented. Several recommendations for carbonate acidizing operation are given. Abstract: We present a two-phase thermal-hydrologic-chemical coupled model for simulating the dissolution process during the acidization of carbonate rocks. In particular, we develop a new model to describe the change in irreducible water saturation, residual oil saturation, and the maximum relative permeability of oil and water phases with dissolution proceeding. We also present a new method for the generation of the initial porosity field with controllable correlation length. In numerical calculation, the sequential iteration approach is adopted to solve the presented model, and the operator splitting method is used to deal with the reaction relevant equations. The involved equations are discretized using the finite-volume method, where the convection term is discretized by the MINMOD scheme which can prevent overshoot/undershoot of the numerical solution. Additionally, sensitivity analysis of the dissolution process concerning rock properties, the exothermic heat of reaction, and two-phase flow, is carried out. Based on the predicted results, several recommendations for the carbonate acidizing operation are given, and the potential extensions of the current work are summarized.